Improving literacy through storytelling in residential care - Irene Stevens; Ruth Kirkpatrick; Claire McNicol (Scottish Journal of Residential Child Care)
The Learning with Care report (HM Inspectors of Schools and the Social Work Services Inspectorate, 2001) highlighted the poor attainment of looked-after children in Scotland. As a result of the report, funding was made available to local authorities to help raise their educational attainment. South Lanarkshire Council used part of this funding to develop a storytelling project. This paper will outline the evaluation of the project, and highlight some of the factors which emerged and which could have wider applications in developing literacy for children and young people in residential child care.